2016
DOI: 10.1155/2016/4153278
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Taboo: Illicit Drug Use among Adolescents with Type 1 Diabetes Mellitus

Abstract: Background. The aim of the study was to explore the prevalence of illicit drug use in a group of Polish adolescents with type 1 diabetes (DM1) in comparison with a national cohort of their healthy peers. Methods. Two hundred and nine adolescents with DM1, aged 15–18 years, were studied in 2013 with an anonymous questionnaire prepared for the European School Survey Project on Alcohol and Other Drugs (ESPAD). The control group was a representative sample of 12114 students at the same age who took part in ESPAD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…This risk is heightened by an apparent association between alcohol consumption, poorer metabolic control, and risk of diabetic ketoacidosis . There is some evidence though that diabetic youth may use illicit or recreational drugs less commonly and smoke less commonly than healthy peers. Smoking in the context of type 1 diabetes during youth is a marker of social deprivation .…”
Section: Alcohol Smoking and Drugsmentioning
confidence: 99%
“…This risk is heightened by an apparent association between alcohol consumption, poorer metabolic control, and risk of diabetic ketoacidosis . There is some evidence though that diabetic youth may use illicit or recreational drugs less commonly and smoke less commonly than healthy peers. Smoking in the context of type 1 diabetes during youth is a marker of social deprivation .…”
Section: Alcohol Smoking and Drugsmentioning
confidence: 99%
“…The risk factors caused by unhealthy lifestyles is not only prevalent among the general population of Iran (24), they are also creating complications among drug addicts (12). Factors such as smoking cigarettes (25), obesity (26), hypertension (27), diabetes (28), malnutrition (29), sedentary lifestyle and lack of mobility (30), as well as stress (31) are prevalent among addicts. Considering that about two-thirds of our patients had poor cardiac risk perception, the likelihood of controlling these risk factors is weak.…”
Section: Discussionmentioning
confidence: 99%
“…The study characteristics of the six included articles are summarized in Table 1. Study designs were cross-sectional (N = 4, 67%) [21,23,24,26], cohort (N = 1, 17%) [22] and case-control (N = 1, 17%) [25]. All studies were published between 2016 and 2018, and the majority were conducted in the USA (N = 4, 67%) [21,22,24,25].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The average age of participants was 16.5 to 39.1 years; one study by Hogendorf et al included only teenage participants (15-18 years of age) while two studies included a mix of teenagers and adults [24,26]; two studies included only adults (> 18 years of age) [21,22] and one study did not report the age of the sample population [25]. Five of the six studies reported gender distributions ranging between 40.2 and 100% female participants [21][22][23][24]26]. Five of the six studies included investigation of T1D (n = 5, 83%) [21][22][23][24]26] while one study examined T2D (N = 1, 17%) [25]; no relevant [21]; another reported a combination of insulin injections and insulin pump therapy [22]; and Wisk et al [26] reported use of insulin pumps, blood sugar testing at least 5 times a day and completing at least 3 HbA1c tests in the past year [26].…”
Section: Description Of Studiesmentioning
confidence: 99%